Associations between Work Intensification, Stress and Job Satisfaction: The Case of Nurses in Ontario - Zeytinoglu, Isik; Denton, Margaret; Davies, Sharon; Baumann, Andrea; Blythe, Jennifer; Boos, Linda (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
Health sector reform of the 1990s affected most health care workers in Ontario and in other provinces. As a result of organizational changes, many workers experienced work intensification. This paper examines the associations between work intensification, stress and job satisfaction focusing on nurses in three teaching hospitals in Ontario. Data come from our 2002 survey of 949 nurses who worked in their employing hospital since the early 1990s when the health sector reform era began. Results show that nurses feel their work has intensified since the health sector reform of the 1990s, and work intensification contributed to increased stress and decreased job satisfaction. Results provide empirical support to the literature which suggests that work intensification has an adverse effect on workers’ health and well-being, and work attitudes.